1996
DOI: 10.1051/gse:19960308
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate restricted maximum likelihood estimation of genetic parameters for production traits in three selected turkey strains*

Abstract: Summary -Genetic parameters related to growth, carcass composition and egg production were estimated on three (two female and one male) commercial strains of turkey using the method of restricted maximum likelihood (REML). In order to account for the sexual dimorphism in turkeys, body weight (BW, measured at 12 and 16 weeks of age) was considered as a sex-limited trait. As many as seven traits were analyzed simultaneously in one strain. Egg numbers were normalized using a Box-Cox transformation. Three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…As observed by Merritt [23] and Ayoub et al [2] in small groups of broilers and by Chapuis et al [7] in a large sample of data on turkeys, heritability appears to be higher for female body weight than for male body weight. Higher residual variance and lower additive genetic variance were observed for male traits.…”
Section: Genetic Parameters Of Growth Traits In Both Sexessupporting
confidence: 49%
“…As observed by Merritt [23] and Ayoub et al [2] in small groups of broilers and by Chapuis et al [7] in a large sample of data on turkeys, heritability appears to be higher for female body weight than for male body weight. Higher residual variance and lower additive genetic variance were observed for male traits.…”
Section: Genetic Parameters Of Growth Traits In Both Sexessupporting
confidence: 49%
“…Ayorinde and Olagbuyiro [2] also reported that clutch size varied from 1 to 12 eggs, and the highest frequency was 72.3% for a 1-3 egg clutch. The Box-Cox transformation of egg production traits resulted in increases in estimated heritability, which were reported by Ibe and Hill [20], Besbes et al [7] and Chapuis et al [13]. In the present study, the estimated heritability values were 0.15 ± 0.01 and 0.42 ± 0.02 for un-transformed and transformed variables, respectively.…”
Section: Data Distribution and Transformationsupporting
confidence: 68%
“…The relative influence of maternal effects is generally moderate in poultry. In turkeys, environmental maternal effects represented , 5.2% to 8% of the total variance of BW at 12 and 16 weeks of age, depending on the strains tested (Chapuis et al, 1996). This result, in addition to the particularities of our pedigree (65% of the 334 dams were of unknown parents), may explain why we were not able to evidence any maternal effects.…”
Section: Resultsmentioning
confidence: 75%
“…Case et al (2010) reported values of 0.35 6 0.02 for the heritability of BW at 15 weeks with the bivariate method. Chapuis et al (1996) reported heritability estimates of 0.77 for female BW and 0.68 for male BW at 16 weeks of age. In the study by Nestor et al (2006), the realised heritability of 16-week BW was 0.202, 0.130 and 0.166 for males, females and both sexes, respectively, during the last generations of selection.…”
Section: Heritabilitymentioning
confidence: 99%